The Micro- and Nano-scale Structure of the Most Superficial Layer of Articular Cartilage - Boyanich, Rebecca Lee (Curtin University, 2022)
This dissertation illustrates the three-dimensional structure and composition of the most superficial layer of healthy sheep articular cartilage to gain understanding of the role of this layer in the tissue’s function. This was achieved by isolating the layer from the underlying cartilage to study using confocal and atomic force microscopy. The imaging techniques studied the microstructure of the most superficial layer. This knowledge can advance our understanding of the aetiology of osteoarthritis and aid the development of tissue regenerative therapies and diagnostic techniques.